The Impact of the Circular Economy on Mitigating the Consequences of Climate Change in the Regions of Ukraine - Kobylynska Tetiana; Hrynchak Nataliia; Motuzka Olena (ECONOMICS)
Climate change and its impact on the economic and social welfare is a vitally important problem explored everywhere in the modern world. The objective of this research is to determine a correlation between the amount of carbon dioxide emissions in Ukrainian regions and their economic and demographic indicators: gross regional product, turnover of business entities and population density. The study is focused on CO2 emissions from stationary pollution source. The article provides evidence-based arguments that circular economy is the model integrating two central objectives: economic growth and mitigation of effects from climate change. The study revealed a strong correlation between the implementation of circular economy practices and objectives of Sustained Development Goas, in particular with respect to minimization of СО2 emissions. A statistical analysis of the relationship between СО2 emissions and gross regional product (GRP), turnover of business entities and population density at the level of Ukrainian regions was made. It was revealed that all the Ukrainian regions with high rates of per capita GRP growth there is no tendency to increase CO2 emissions. This complies with circular economy priorities: minimization of resource extraction through processing and re-production. The regions with a higher population density were revealed to have lower СО2 emissions, which can be attributed to the fact that a higher population density often entails a more compact urban habitat. The regions with the largest turnover of business entities include regions with their highest population density. Economically developed regions often push technological innovations with breakthrough effects for energy technologies, transport and industrial processes, which help reduce CO2 emissions.